Ideal‐Typical Utility Infrastructure at Chemical Sites – Definition, Operation and Defossilization. Issue 6 (2nd March 2022) - Bauer, Thomas; Prenzel, Marco; Klasing, Freerk; Franck, Rüdiger; Lützow, Julian; Perrey, Karen; Faatz, Rainer; Trautmann, Juliane; Reimer, Andreas; Kirschbaum, Stefan
Abstract: The defossilization of the electricity and heat supply in the chemical industry poses a significant challenge. In particular, the intended feed‐in of volatile renewable electricity into the chemical processes may conflict with the need for a constant, secure and affordable electricity and heat supply for chemical plants. Adapted concepts for the operation of the cogeneration plant, which is located at the chemical site, play a central role. The present work defines a so‐called ideal‐typical utility infrastructure (iUI). The iUI is a means to exemplarily investigate the operational behavior of utility infrastructures and furthermore to identify defossilization options for process steam and electricity supply at chemical sites. Abstract : The defossilization of the chemical industry, in combination with an increasing share of renewable volatile electricity as well as rising gas prices, is a significant challenge. A so‐called ideal‐typical utility infrastructure is defined, which serves as a basis for the investigation of CO2 reduction options. Promising CO2 reduction strategies are qualitatively illustrated and discussed.